Food effects on gastrointestinal physiology and drug absorption - Kambayashi, Atsushi; Shirasaka, Yoshiyuki (Drug metabolism and pharmacokinetics, 2023)
Food ingestion affects the oral absorption of many drugs in humans. In this review article, we summarize the physiological factors in the gastrointestinal (GI) tract that affect the in vivo performance of orally administered solid dosage forms in fasted and fed states in humans. In particular, we discuss the effects of food ingestion on fluid characteristics (pH, bile concentration, and volume) in the stomach and small intestine, GI transit of water and dosage forms, and microbiota. Additionally, case examples of food effects on GI physiology and subsequent changes in oral drug absorption are provided. Furthermore, the effects of food, especially fruit juices (e.g., grapefruit, orange, apple) and green tea, on transporter-mediated permeation and enzyme-catalyzed metabolism of drugs in intestinal epithelial cells are also summarized comprehensively.